Pengaruh Kompensasi dan Lingkungan Fisik terhadap Kepuasan Kerja dan Kinerja Karyawan: Studi pada CV Garuda Plastik - Rizky, Agustiya Fatriya (Jurnal Ilmiah Aset, 2024)
This research proposal was put forward to identify how the effect of compensation on job satisfaction, the effect of the physical environment on job satisfaction, the effect of job satisfaction on employee performance. The type of research that will be carried out is explanatory research or explanatory research where this research aims to analyze the relationship between exogenous variables and endogenous variables. Exogenous variables in this study include compensation, physical environment and work satisfaction, while the endogenous variables are employee performance. The population to be analyzed in this research proposal is 133 production and office employees of CV Garuda Plastik in the Demak area. The sample in this study was determined using a purposive sampling method with a total of 100 respondents. For the research analysis method used is a quantitative analysis method using multiple linear regression analysis. The supporting application program used is SPSS 22. The results of the study show that compensation has a positive and significant effect on job satisfaction. The physical environment has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance